A IMPLEMENTATION OF ISLAMIC VALUES EDUCATION IN MORAL LEARNING AT MADRASAH IBTIDAIYAH AL-HIDAYAH PANGKALAN TASIKMALAYA : pendidikan nilai-nilai islam - maryana, ina (CV. Media Publikasi Profesional, 2024)
Abstract: This research aims to examine the implementation of Islamic values ​​education in moral learning at Madrasah Ibtidaiyah Al-Hidayah Pangkalan, Tasikmalaya. Islamic values ​​education is an integral part in forming students' character based on the teachings of the Islamic religion. This research aims to examine the implementation of Islamic values education in moral learning at Madrasah Iibtidaiyah Al-Hidayah Pangkalan Tasikmalaya. Using a descriptive qualitative approach, this research focuses on the process and effectiveness of implementing Islamic values, such as honesty, responsibility, courtesy and tolerance in forming student character. Data was collected through observation, interviews with teachers and students, as well as documentation of school activities. The results of the research show that Islamic values education at Madrasah Ibtidaiyah Al-Hidayah has succeeded in forming students' Islamic character through the integration of these values in moral learning. Teachers act as role models, and daily activities such as group prayer, congregational prayers, and community service familiarize students with applying moral values in everyday life. The application of these values has a positive impact, both at school and in the family environment, which is marked by increased attitudes of discipline, responsibility and mutual respect among students. The conclusion of this research is that the implementation of Islamic values education at Madrasah Ibtidaiyah Al-Hidayah is effective in forming the character of students who have noble morals and are ready to practice Islamic values in life. Abstrak: Penelitian ini bertujuan untuk mengkaji implementasi pendidikan nilai-nilai Islam dalam pembelajaran akhlak di Madrasah Ibtidaiyah Al-Hidayah Pangkalan, Tasikmalaya. Pendidikan nilai-nilai Islam merupakan bagian integral dalam pembentukan karakter siswa yang berlandaskan pada ajaran agama Islam. Penelitian ini bertujuan untuk mengkaji implementasi pendidikan nilai-nilai Islam dalam pembelajaran akhlak di MI Al-Hidayah Pangkalan Tasikmalaya. Dengan menggunakan pendekatan kualitatif deskriptif, penelitian ini berfokus pada proses dan efektivitas penerapan nilai-nilai Islam, seperti kejujuran, tanggung jawab, sopan santun, dan toleransi dalam pembentukan karakter siswa. Data dikumpulkan melalui observasi, wawancara dengan guru dan murid, serta dokumentasi kegiatan sekolah. Hasil penelitian menunjukkan bahwa pendidikan nilai-nilai Islam di Madrasah Ibtidaiyah Al-Hidayah berhasil membentuk karakter islami siswa melalui integrasi nilai-nilai tersebut dalam pembelajaran akhlak. Guru berperan sebagai teladan, dan kegiatan sehari-hari seperti doa bersama, salat berjamaah, dan kerja bakti membiasakan siswa menerapkan nilai-nilai akhlak dalam kehidupan sehari-hari. Penerapan nilai-nilai ini berdampak positif, baik di sekolah maupun di lingkungan keluarga, yang ditandai dengan meningkatnya sikap disiplin, tanggung jawab, dan saling menghargai di kalangan siswa. Kesimpulan penelitian ini adalah bahwa implementasi pendidikan nilai-nilai Islam di MI Al-Hidayah efektif dalam membentuk karakter siswa yang berakhlak mulia dan siap mengamalkan nilai-nilai islami dalam kehidupan.